Innovation, evaluation and measurement: macro-level and firm-level perspectives - Caetano, I. (The Quadruple Innovation Helix Nexus, 2017)
Innovation is recognised as a difficult domain to assess and to measure. Innovation indicators are necessary to characterise innovation dynamics and to assess the effects of public policies supporting innovation or, from a micro perspective, return on investment, including the creation of conditions conducive to research, development and innovation activities. Moreover, it is also important to observe the role of the different actors, whether companies, the main drivers of innovation, or other entities in the innovation system. At country level, research has highlighted the importance of analysing innovation performance. Also, several studies have focused approaches developed by international organisations, in particular the European Commission. Part I of this chapter relates to a macro-level perspective applied to innovation measurement. Companies are eager to develop and apply methodologies contributing to capture innovation results. A problem in innovation management is how to do it. A framework model was proposed and applied, considering three levels of evaluation of innovation activities and projects, following a Return on Investment approach. Part II of this chapter aims to analyse how companies are managing innovation, which practices have been implemented and what framework could be designed to promote their capabilities to evaluate and measure innovation. It will contribute to the understanding of innovation measurement at firm level and to a more systematic approach for innovation management.